SEJARAH DAN FUNGSI RUMAH GODANG PADA SUKU JIN TANJUNG DI KENEGERIAN SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Arzyka, Zhila Tahta; Isjoni, Isjoni; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study is (1) To know the historical background of the establishment of the Godang House in Jin Tanjung clan in Kenegerian Sentajo Sentajo sub district of Kuantan Singingi district (2) To know the function of the Godang House in the Jin Tanjung clan in Kenegerian Sentajo Subdistrict of Sentajo Raya Regency of Kuantan Singingi (3) the role of Rumah Godang in the Jin Tanjung clan in Kenegerian Sentajo Sentajo Subdistrict District of Kuantan Singingi (4) To find out how the existence of the Godang House in Jin Tanjung clan in Kenegerian Sentajo Subdistrict Sentajo Raya Regency of Kuantan Singingi.Godang House of Jin Tanjung Clanis one of the cultural heritages of the Kuantan Singingi District which still stands up to the present.The early history of the Godang House of the Jin Tanjung clan is inseparable from its place of origin, namely the Minangkabau country (West Sumatra). This study also compares how the shape of the Godang House in Sentajo Raya with the original Gadang House from West Sumatra.Not only serves as a gathering place for one clan, but also serves as a place for Adat law. The type of this research is field research, which means that research is carried out by going directly to the field to explore and examine data relating to the title. The respondents in this study were Datuk Penghulu, Dubalang and those who knew about the existence of the Godang House of the Jin Tanjung clan. While the data collection techniques in this study were conducted using two methods, namely interviews and documentation studies. The results showed that the Godang House of the Jin Tanjung clan had a large function and role in advancing the Sentajo Raya people.Key Words: Godang House, Sentajo Raya, Kuantan Singingi